Preparation of Xanthine Oxidase Inhibitory Peptide from Black Bean Protein by Enzymatic Hydrolysis and Its Uric Acid-Lowering Activity in Vitro - SUN Jingru, SUN Mingshuang, LÜ Wenqing, CAO Rong’an, DIAO Jingjing, WANG Changyuan (Shipin Kexue)
In this study, black soybean protein was enzymatically hydrolyzed to prepare xanthine oxidase (XOD) inhibitory peptide. Based on XOD inhibitory activity and degree of hydrolysis (DH), various proteases were screened, and the hydrolysis parameters were optimized. Furthermore, the protein hydrolysate was fractionated by membrane separation into several fractions. The molecular mass ranges of the resulting fractions were determined based on XOD inhibitory activity, and their amino acid composition, molecular mass distribution, peptide sequences, activity and stability were analyzed. The results showed that the optimum enzymatic hydrolysis conditions were as follows: alkaline protease dosage of 1.5%, hydrolysis time of 4 h, temperature of 50 ℃, pH 9.0, and substrate concentration of 3%. Under the optimized conditions, the XOD inhibition rate and DH of the protein hydrolysate were 73.61% and 21.29%, respectively. The XOD inhibitory activity of F3, obtained from ultrafiltration of the hydrolysate, was the highest (with a half-maximal inhibitory concentration (IC50) of 8.76 mg/mL), with the molecular mass ≤ 1 500 Da. In F3, hydrophobic and basic amino acids accounted for 56.66% and 20.16% of the total amino acids, respectively. This fraction had good stability under high-temperature treatment, simulated gastric and trypsin digestion. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) identified 18 peptides in F3, with an average molecular mass of approximately 500–1 400 Da. In these peptides, hydrophobic amino acids at the N-terminus and C-terminus accounted for 44.86% and 33.14%, respectively, and basic amino acids accounted for 33.57% and 39.29% of the total amino acid residues, respectively. The results of this study provide a theoretical basis for the high value utilization of black bean protein.